Educación centrada en la persona y fortalecimiento de capacidades actitudinales de los estudiantes de la Escuela Democrática de Huamachuco, 2021 - Infantes Encarnación, Leslie Julissa (2023)
The main objective of this research was to analyze how person-centered democratic education strengthens the attitudinal capacities of: freedom of decision, autonomy, and intercultural dialogue, of the students of the Democratic School of Huamachuco, year 2021. Regarding the methodology used: it is a qualitative study, cross-sectional non-experimental design; A sample of 13 students and 6 companions was included, with a total of 19 people from the Escuela Democrática de Huamachuco-EDHU; The following techniques were used: participant observation, in-depth interview, bibliographic compilation and photographic record, the instruments being the interview guide and record, observation guide and photographic camera. Regarding the methods used, it was considered: ethnographic, phenomenological, deductive and inductive. According to the results obtained in this research, it is concluded that person-centered democratic education strengthens the attitudinal capacities of: freedom of decision, autonomy and intercultural dialogue of EDHU students, through the practice of the fundamental pillars of: freedom to learn, self-directed learning, active community participation-assemblies, horizontal relationship, gender equality and respect for diversity. Allowing the recognition and appreciation of students as human beings, active subjects of rights, protagonists of their own history, with determination, who know their talents and interests, capable of exercising their freedom with responsibility and commitment, of valuing and respecting the differences of the other and see in the other person a unique and unrepeatable being.